Roses Pests And Their Control - Haytmuratov Arslanbek Faizullaevich (Zien Journals, 2023)
The article studied the bioecology and harmfulness of aphids, spider mites, thrips, lump worms, pink borer, pink sawfly on different varieties of roses in the conditions of the Termez region, noted aphids, lump worm and pink borer as the dominant pest species, and recommendations were given. to fight them.
Keywords: Rose; plant; pest; aphid